Morphogenesis of Fractofusus andersoni and the nature of early animal development - Frances. S. Dunn; Philip C. J. Donoghue; Alexander G. Liu (Nature Communications)
Abstract Rangeomorphs are among the oldest anatomically complex macroscopic fossil organisms and, originating prior to 574 Ma, they represent the earliest total-group eumetazoans. Rangeomorph morphogenesis is therefore significant for understanding the early diversification of eumetazoan bodyplans. However, previous analyses of rangeomorph development have focused on uniterminal forms (possessing only one frond), leaving biterminal and multiterminal rangeomorph bodyplans poorly understood. We describe a population of the biterminal rangeomorph Fractofusus andersoni from the Mistaken Point Ecological Reserve UNESCO World Heritage Site of Newfoundland, Canada, and construct a model of growth in F. andersoni that rationalises variation between Fractofusus, Charnia, Bradgatia and other rangeomorphs, providing a framework for explaining evolutionary transitions between the bodyplans of these members of the eumetazoan stem-group. Our results imply that complex developmental regulatory machinery was already being utilised during the late Ediacaran in the earliest-diverging eumetazoan taxa represented in the fossil record.